A Qualitative Study of Determinant Stunting Among Children Under Five in Sungai Gerong Village - Anita Rahmiwati; Fenny Etrawati; Yuliarti Yuliarti; Ira Dewi Ramadhani; Erike Septa Prautami; Devy Yuliantari; Devy Kartika Sari; Virgina Putri Sabila; Dwi Ananda Putri; Risa Nur Amalia (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2026)
Stunting remains a major public health problem in Indonesia, including in Banyuasin Regency, which is a priority area for stunting prevention. Sungai Gerong Village in Banyuasin I District reports a relatively high prevalence of stunting among children under five. This study aimed to explore the determinants of stunting in this village. A qualitative descriptive design was employed to examine behavioral and environmental factors contributing to stunting. Data were collected through in-depth interviews with 10 key informants, including four health workers and community leaders and six mothers of stunted toddlers. The study explored environmental conditions, child feeding practices, parenting patterns, and household food security. Dietary intake was assessed using a Food Frequency Questionnaire (FFQ), and household food security was measured using the Food Consumption Score (FCS).The findings revealed that most toddlers lived in inadequate environmental conditions and consumed predominantly high-carbohydrate diets with low intake of vegetables and animal protein. Three households were classified as food insecure. Parenting practices were suboptimal, particularly regarding appropriate feeding practices and cognitive stimulation. Poor sanitation, limited dietary diversity, inadequate caregiving practices, and restricted household food access were identified as key contributing factors.These findings suggest that stunting in Sungai Gerong Village is driven by multidimensional factors requiring integrated interventions. Policy and practical efforts should focus on strengthening nutrition education for caregivers, improving sanitation infrastructure, enhancing access to diverse and affordable nutritious foods, and reinforcing community-based nutrition services. Cross-sectoral collaboration is essential to sustainably reduce stunting prevalence in this area.